The Implementation of International Law on Strengthening Cooperation in Combating Money Laundering Crimes of ASEAN Countries - Wiranto, Agus Prasetia; Hafidz, Jawade (Jurnal Daulat Hukum, 2024)
The development of technology that is growing rapidly and continues to increase makes criminals smarter and more creative in conducting money laundering. It is one of the transnational crimes because it is a crime that allows the perpetrators to commit criminal acts outside the country's borders. In 2022-2023 Indonesia has eradicated money laundering, ranging from those originating from narcotics, gambling, investment fraud, environmental crimes, banking, and cybercrime. This effort succeeded in uncovering 242 money laundering cases with 161 suspects and recovering state losses of IDR 3.74 trillion. So, the research discussed how the implementation of international law in strengthening cooperation in combating money laundering in ASEAN countries is. This research method was normative research with legal research as a process in finding legal rules, legal principles, and legal doctrines. The results of the research that has been done can be concluded that in Strengthening cooperation in eradicating money laundering in ASEAN region by making agreements (treaties) and implementing treaties on Mutual Legal Assistance in Criminal Matters 2004 (MLAT 2004) among ASEAN countries with the concept of free movement of judgment in the field of criminal matters and Strengthening inter-state ties politically to eradicate transnational crimes, especially money laundering in ASEAN member countries for cross-country law enforcement and implementing the principle of aut punire aut dedere.